2021
DOI: 10.1002/esp.5290
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic carbon concentrations and fluxes in a degraded blanket peatland with piping and pipe outlet blocking

Abstract: Soil piping is an important agent of erosion in many environments, including blanket peatlands. Peatland restoration that aims to reduce erosion has mainly focussed on revegetation and blocking ditches and gullies, rather than reducing erosion from natural soil pipes. However, little is known about the contribution of pipeflow to the fluvial carbon budget of degraded blanket peatlands and whether it is possible to moderate it. In a heavily degraded blanket bog, dissolved and particulate organic carbon (DOC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 69 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…Up to now, carbon loss in piping‐affected areas have been only studied in peatlands as these areas represent important global carbon stores (i.e., Billett et al, 2012; Dinsmore et al, 2011; Holden, 2005b, 2006; Regensburg et al, 2021). Generally, it has been suggested that pipes in peatlands play a dynamic (short‐term) and changing (long‐term) role in carbon loss and they release the terrestrially produced greenhouse gases [carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous oxide (N 2 O)] to the atmosphere (Dinsmore et al, 2011).…”
Section: The Role Of Soil Piping In Carbon Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…Up to now, carbon loss in piping‐affected areas have been only studied in peatlands as these areas represent important global carbon stores (i.e., Billett et al, 2012; Dinsmore et al, 2011; Holden, 2005b, 2006; Regensburg et al, 2021). Generally, it has been suggested that pipes in peatlands play a dynamic (short‐term) and changing (long‐term) role in carbon loss and they release the terrestrially produced greenhouse gases [carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous oxide (N 2 O)] to the atmosphere (Dinsmore et al, 2011).…”
Section: The Role Of Soil Piping In Carbon Cyclementioning
confidence: 99%
“…A recent study has revealed that pipes potentially contribute c . 56% of DOC exported by the stream in degraded blanket peatlands (Regensburg et al, 2021).…”
Section: The Role Of Soil Piping In Carbon Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…The error in this load estimate is then assessed using the variance in the flow-weighted mean concentration (Hope et al, 1997 ). Recent examples of this technique being employed to estimate DOC loads or fluxes include Arízaga-Idrovo et al, 2022 ; Gaffney et al, 2020 , Pérez-Rodríguez & Biester, 2022 , Regensburg et al 2022 ; Rosset et al, 2019 and our own work in Ritson et al, 2019 .…”
Section: Introductionmentioning
confidence: 99%